Elective caesarean delivery adversely affects preductal oxygen saturation during birth transition. Issue 4 (7th December 2015) - Zanardo, Vincenzo; Dal Cengio, Valentina; Parotto, Matteo; Cavallin, Francesco; Trevisanuto, Daniele
Abstract : Objective: To compare preductal oxygen saturation (SpO2 ), heart rate (HR) and cord blood pH after birth in healthy term neonates delivered by elective caesarean delivery (CD) and vaginal delivery (VD), managed according to 2010 Neonatal Resuscitation Guidelines. Design: In a prospective cohort study, sensors were placed on the right hand of the neonate. Setting: III level Maternity ward of the Department of Obstetrics and Gynaecology of Padua University, Padua, Italy. Main outcome measures: SpO2 and HR were recorded during the first 10 min after birth. Umbilical artery blood gas analysis was obtained immediately after delivery. Patients: We studied 60 newborn infants by elective CD and 60 by VD. Results: The SpO2 gradually significantly improved during the first 10 min of life (p<0.0001), with a trend towards a slower increase in caesarean-delivered neonates (p=0.09) (Friedman's two-way non-parametric analysis of variance (ANOVA)). Instead, HR varied during the first 10 min of life (p=0.001) without significant difference between the two delivery groups (p=0.41). Umbilical artery pH values were lower in VD (p=0.005). At 10th minute, elective CD had a significantly negative effect on SpO2 (ß=−2.44; 95% CI −4.52 to −0.36; p=0.02) with respect to VD. Conversely, at 10th minute, delivery mode had no statistically significant effect on HR (ß=0.33; 95% CI −9.39 to 10.01; p=0.95). Conclusions: In healthy term neonates, the SpO2 gradually improved during the first 10 min of life. At 10th minute, elective CD had a significantly negative effect on SpO2, but these changes did not result in an impaired HR pattern.